KEMANDIRIAN PEMBUDIDAYA IKAN PATIN DI LAHAN GAMBUT DI DESA TANGKIT BARU, KEC. KUMPE ULU, KABUPATEN MUARO JAMBI PROVINSI JAMBI - Aprolita Aprolita; Siti Amanah; Djoko Susanto (Jurnal Penyuluhan, 2008)
Self reliance of the patin fish farmers in Tangkit Baru Village is very important to promote better quality of life. Self reliance of the fish farmers reflected ability of them in coping the problems and finding out of alternatives solution. The objectives of the study were: (1) To indentify the characteristics of patin fish farmers in peatlands, (2) To analyze self reliance of the patin fish farmers in managing of aquaculture, (3) To analyze the relationship between the self reliance of the patin fish farmers and their characteristics. Population of this study were the patin fish farmers in Tangkit Baru. The number of the respondens were 69 patin fish farmers in Tangkit Baru which were taken by simple random sample. The data were collected on May to July 2007. The data were analyzed by using Correlation Spearman. The results of the study were: (1) Cultivation of patin fish in Tangkit Baru village is very successful. The fish farmers could modify their business well, as they conducted their budiness independently, (2) Patin fish farmers have been done a good action in capital management, production process and marketing, (3) There were significant relation between self reliance of the patin fish farmers and their characteristics, namely in formal education, motivation, family dependent members, cosmopolite, man power, and experience in business.